Effect of Heat Treatment on Whey Proteins Denaturation in the Presence and Absence of Lactose - Al-Saadi, Jasim M.S. (Sulaimani Journal for Pure and Applied Sciences, 2014)
The effect of lactose on denaturation of whey proteins was investigated in cow milk, with and without lactose, heated at different temperatures ranged of (65-95)°C for 30 min. Compared with the milk without, the milk containing lactose showed a smaller increase in pH values and a higher concentration of whey proteins. Whey proteins percentage in milk samples with and without lactose heated at (65,70,75 ,80,85,90 and 95) °C for 30 min were(90.38,88,86.16 , 67.9,44,23,23.5 and 23.2%) and (82.85,75, 71.14 , 44.18,25.92,20.52 and 20%) respectively. It was concluded that heating cause formation new band located below β-Lg band in whey samples of both milk ,with and without lactose , and the intensity of this band increased with increment of heating temperatures and heating time.
Keywords: milk proteins; heat treatment; whey proteins; denaturation